Pelatihan Microsoft Excel Untuk Peningkatan Soft Skills Anggota Perhimpunan Human Resources Development Jawa Tengah - Istiawan, Deden; Huda, Nurul; Mahiruna, Adiyah; Ngatimin, Ngatimin; Prayogi, Sukmono Yogi (Intimas, 2024)
Microsoft Excel is a spreadsheet program that allows users to create, manage, and analyze data in a table or worksheet format. Microsoft Excel is useful for performing various business tasks such as inventory management, financial report generation, budget planning, and more. The utilization of Microsoft Excel applications for data processing plays a very crucial role in the world of work. This community service activity aims to improve the skills and understanding of members of the Central Java HRD Association in the use of Microsoft Excel. Through this training, participants will have the ability to optimize the utilization of Excel and increase productivity in their daily activities. In addition, the Microsoft Excel intermediate level training also provides participants with the opportunity to understand basic programming concepts. The evaluation results showed a positive level of acceptance from participants on the suitability and usefulness of the material presented. The majority of participants indicated high satisfaction with the training, indicating improved skills in using Microsoft Excel. This community service activity succeeded in having a positive impact in improving the competence of Central Java HRD Association members in utilizing Microsoft Excel technology in their scope of work.